On the Integration of Hydrogen in multipurpose wave energy platforms (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This work presents an integrated numerical modelling approach implemented in Modelica language, which combines a multipurpose wave energy floating platform made of multiple oscillating water columns and the production and storage of green hydrogen in the same platform. The modelling approach comprised the simulation of the platform in WAMIT from which the hydrodynamic coefficients were obtained that serve as input for the integrated model implemented in Modelica. The Cherry Library for electrolysis processes and new modules developed in this work for storage were used and coupled to a model for the five-oscillating-water-column floating platform. The optimisation of hydrogen production based on hydrodynamic performance and energy conversion from waves off the coast of Portugal was conducted to identify optimal green hydrogen production parameters. The operational performance of the system was studied in detail for four representative days of the seasons to estimate optimal production of green hydrogen from ocean waves under those conditions. Dispatch of hydrogen and its conversion to other sustainable fuels, such as methanol or Ammonia are also discussed in terms of the total levelised cost of hydrogen (LCOH). A new tool developed at the National Laboratory for Energy and Geology was implemented to estimate costs. Results are still under progress.